Will robots take your job? a plea for consensus - Nigel M. de S. Cameron (Cambridge Polity Press, 2017)
The trend that began with ATMs and do-it-yourself checkouts is moving at lightning speed. Everything from driving to teaching to the care of the elderly and, indeed, code-writing can now be done by smart machines. Conventional wisdom says there will be new jobs to replace those we lose ? but is it so simple? And are we ready?
Includes bibliographical references and index.
Keywords: Labor supply -- Effect of technological innovations on; Technological innovations -- Social aspects; Automation; SCIENCE / Philosophy & Social Aspects